Trematodes and Major Trematodoses of Small Cattle in Various Regions of Uzbekistan - Dadaev, S. D.; Paluaniyazova, D. A.; Yesimbetov, A. T. (UTTAR PRADESH JOURNAL OF ZOOLOGY, 2023)
Animal husbandry in Uzbekistan is one of the leading branch of the national economy. The resulting products occupy a large share among consumer goods. Currently, due to the spread of some parasitic diseases, including trematodes, there is a decrease in a number of quantitative indicators in the livestock farms of the Republic. Consequently, flukes are of great practical importance. They parasitize almost all organs of farm animals, including small cattle, causing serious diseases of animals in certain regions of Uzbekistan.